Preparation method of aramid fiber mica paper

By combining wet molding and mechanical compression methods, and using acetic acid surface treatment and layered structure design, the problems of uneven dispersion and insufficient interface bonding force in the prior art are solved, and high-performance aramid fiber mica paper preparation is achieved.

CN119859936AInactive Publication Date: 2025-04-22HUNAN DINGTIANYUE NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510055470.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-22
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing preparation methods of aramid fiber mica paper, the molding process relies on a single wet molding or mechanical compression, making it difficult to achieve uniform dispersion and densification of aramid fiber and mica powder, resulting in uneven microstructure of the material, affecting the mechanical properties and insulating properties.

Method used

Using a method combining wet molding and mechanical compression, the interface bonding between aramid fiber and mica powder is enhanced by acetic acid surface treatment, and the ratio of fiber and mica powder at different levels is controlled through layered structure design to achieve gradient structure aramid fiber mica paper.

Benefits of technology

It significantly improves the microstructure uniformity of the material, enhances the mechanical strength, insulation properties and heat resistance of the composite material, reduces production costs and environmental impacts, and improves the overall stability and durability of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of aramid fiber mica paper, and relates to the technical field of aramid fiber mica paper preparation. The preparation method of the aramid fiber mica paper specifically comprises the following steps: S1, preparing raw materials; s2, aramid fiber surface treatment; s3, carrying out wet molding; s4, forming and preliminary dehydration; s5, carrying out mechanical compression; s6, designing a layered structure; and S7, drying and curing. According to the technology, uniform dispersion and high densification of the aramid fibers and the mica powder are achieved through wet-process forming and multi-layer structural design, the mechanical strength, the insulating property and the heat resistance of the composite material are remarkably improved, the interface bonding force of the fibers and particles can be improved through the interface enhancing technology, complex chemical treatment is avoided, and the composite material is suitable for being used for a large-scale industrial production. The production cost and the environmental burden are reduced, the multifunctionality of the material is optimized through the multi-layer structure, the chemical corrosion resistance and the dimensional stability are enhanced, the layering phenomenon is prevented through unique proportion control and interlayer binding force, and the overall reliability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aramid fiber mica paper preparation, in particular to a method for preparing aramid fiber mica paper. Background Art

[0002] Mica paper is a thin sheet material made by a wet molding process after mica fragments or mica powder is crushed, cleaned, graded, etc., dispersed in water and added with adhesive. It retains the excellent electrical insulation performance, high temperature resistance, chemical stability and flexibility of natural mica, and is mainly used as electrical insulation and high temperature resistant materials. Aramid fiber mica paper is based on mica paper. By adding aramid fiber (such as aramid 1313 or aramid 1414) during the manufacturing process, the high strength, high heat resistance and good electrical insulation performance of aramid fiber are utilized to make the composite material have better mechanical strength and heat resistance, while maintaining the excellent insulation properties of mica, which is suitable for high temperature insulation and mechanical reinforcement occasions with higher requirements. The existing aramid fiber mica paper preparation method generally includes the following steps: first, the aramid fiber is surface treated to improve its bonding force with mica, then the mica powder and the treated aramid fiber are dispersed in water, the two are evenly mixed and molded by a wet molding process, followed by mechanical compression dehydration and curing, and finally the finished aramid fiber mica paper is obtained by drying and hot pressing.

[0003] In the preparation process of aramid fiber mica paper, the molding process usually relies on a single wet molding or mechanical compression method. These methods are difficult to achieve uniform dispersion and densification of aramid fiber and mica powder when processing the mixed slurry. Because aramid fiber and mica particles have large differences in density, particle size and surface properties, the mixed slurry is prone to precipitation or aggregation of fibers and particles during dehydration molding, resulting in uneven material microstructure, which in turn affects the mechanical properties and insulation properties of the composite material. Secondly, interface enhancement technology mainly relies on complex chemical treatment methods, such as the use of surface modifiers or coupling agents. Although these methods can improve the interface bonding force to a certain extent, the effect is often unstable, and it increases production costs and environmental burdens, making it difficult to be widely used in actual large-scale production. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a method for preparing aramid fiber mica paper, which solves the problem that a single molding method in the prior art is difficult to take into account both the uniformity and density of the material and the interface bonding force is weak.

[0005] To achieve the above objectives, the present invention is implemented through the following technical scheme: a method for preparing aramid fiber mica paper, specifically comprising the following steps:

[0006] S1. Raw material preparation

[0007] Prepare raw materials: aramid fiber: 20-30 parts, mica powder: 70-80 parts, carboxymethyl cellulose: 0.5-1.0 parts, acetic acid: 1-5 parts, deionized water: 50-80 parts, vitamin C: 0.1-0.2 parts;

[0008] S2. Surface treatment of aramid fiber

[0009] The aramid fiber was immersed in an acetic acid solution and stirred at room temperature for 1 hour. After treatment, the fiber was thoroughly washed with deionized water until it was neutral, so that active groups were generated on the surface of the aramid fiber, thereby enhancing the interfacial bonding between the fiber and the mica particles.

[0010] S3. Wet Forming

[0011] Prepare aramid fiber, mica powder, carboxymethyl cellulose and deionized water. Add aramid fiber and mica powder into deionized water under stirring conditions, and then add carboxymethyl cellulose. The stirring speed is controlled at 500-800 r / min and the stirring time is 10-15 minutes.

[0012] S4. Forming and initial dehydration

[0013] The mixture is poured into a pre-prepared mold, and a suction filtration device, a Buchner funnel, is used to perform preliminary dehydration under negative pressure conditions, and then preliminary molding is performed;

[0014] S5. Mechanical compression

[0015] Using a mechanical press or roller press, the initially dehydrated material is gradually compressed in the press;

[0016] S6. Hierarchical structure design

[0017] During the molding process, aramid fiber and mica powder were added in different proportions in layers to design aramid fiber mica paper with a gradient structure;

[0018] S7. Drying and curing

[0019] Carefully take out the formed aramid fiber mica paper, place it on a drying rack, and use an oven to dry it. The temperature is controlled between 100-120°C and the drying time is 2-4 hours.

[0020] Preferably, in the raw material preparation of step S1, the aramid fiber is preferably chopped fiber with a length of 3-6 mm and a diameter of 12-15 μm, the mica powder particle size is 50-100 μm, and the acetic acid concentration is 5%.

[0021] Preferably, in the wet forming step S3, the solid content of the mixture is controlled at 3-5wt%, and the pH value is adjusted to 6-7.

[0022] Preferably, in the molding and preliminary dehydration in step S4, preliminary dehydration is performed under a negative pressure of -0.05 MPa, the dehydration time is 5-10 minutes, and the thickness after preliminary molding is controlled to be 2-3 mm.

[0023] Preferably, in the mechanical compression of step S5, the initial pressure is 0.5 MPa, which is gradually increased to 2.0 MPa, the compression time of each stage is 5-10 minutes, and the thickness of the compressed material is controlled to be 0.5-1.0 mm.

[0024] Preferably, in the layered structure design of step S6, the content of mica powder in the surface layer is increased to 80-85wt% to improve the insulation performance, and the content of aramid fiber in the inner layer is increased to 30-35wt% to improve the mechanical strength and toughness.

[0025] Preferably, the drying and curing in step S7 also includes hot pressing curing, specifically, the hot pressing temperature is controlled between 120-150° C., the pressure is 1-2 MPa, and the time is 10-15 minutes.

[0026] The present invention provides a method for preparing aramid fiber mica paper, which has the following beneficial effects:

[0027] The present invention provides a method for preparing aramid fiber mica paper. The present invention effectively solves the problems of uneven dispersion and insufficient densification existing in the traditional process by controlling the mixing ratio and dispersion uniformity of aramid fiber and mica powder, thereby greatly improving the microstructure uniformity of the material and significantly enhancing the mechanical strength, insulation performance and heat resistance of the composite material. In addition, the present technology optimizes the interface bonding force between aramid fiber and mica particles through interface enhancement treatment, without relying on complex chemical modification methods, thereby reducing production costs and environmental impacts. The multi-layer structure design not only achieves an optimized combination of mechanical properties and insulation properties, but also gives the material excellent chemical corrosion resistance and dimensional stability. Through proportion control and optimized interlayer bonding technology, the common stratification problem in traditional stratified design is effectively avoided, and the overall stability and durability of the material are further improved. Therefore, the aramid fiber mica paper prepared by the present technology exhibits excellent comprehensive performance in the application fields of electrical insulation, high temperature resistance and corrosion resistance with high performance requirements, and has significant application advantages and market potential. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] The embodiment of the present invention provides a method for preparing aramid fiber mica paper, which specifically comprises the following steps:

[0031] S1. Raw material preparation

[0032] Prepare raw materials: 20 parts of aramid fiber, 70 parts of mica powder, 0.5 parts of carboxymethyl cellulose, 1 part of acetic acid, 50 parts of deionized water, and 0.1 parts of vitamin C. The aramid fiber is preferably chopped fiber with a length of 3 mm and a diameter of 12 μm. The mica powder has a particle size of 50 μm and an acetic acid concentration of 5%.

[0033] S2. Surface treatment of aramid fiber

[0034] The aramid fiber was immersed in an acetic acid solution and stirred at room temperature for 1 hour. After treatment, the fiber was thoroughly washed with deionized water until it was neutral, so that active groups were generated on the surface of the aramid fiber, thereby enhancing the interfacial bonding between the fiber and the mica particles.

[0035] S3. Wet Forming

[0036] Prepare aramid fiber, mica powder, carboxymethyl cellulose and deionized water, add aramid fiber and mica powder into deionized water under stirring conditions, then add carboxymethyl cellulose, control the stirring speed at 500 r / min, the stirring time for 10 minutes, control the solid content of the mixture at 3wt%, and adjust the pH value to 6;

[0037] S4. Forming and initial dehydration

[0038] The mixture was poured into a pre-prepared mold, and a suction filtration device, a Buchner funnel, was used for preliminary dehydration under negative pressure, and then preliminary molding was performed, and preliminary dehydration was performed under negative pressure of -0.05MPa for 5 minutes, and the thickness after preliminary molding was controlled at 2mm;

[0039] S5. Mechanical compression

[0040] Use a mechanical press or rolling equipment to gradually compress the material after preliminary dehydration in the press. The initial pressure is 0.5MPa, which is gradually increased to 2.0MPa. The compression time for each stage is 5 minutes, and the thickness of the compressed material is controlled at 0.5mm.

[0041] S6. Hierarchical structure design

[0042] During the molding process, aramid fiber and mica powder are added in different proportions in layers to design aramid fiber mica paper with a gradient structure. The mica powder content in the surface layer is increased to 80wt% to improve the insulation performance, and the aramid fiber content in the inner layer is increased to 30wt% to improve the mechanical strength and toughness.

[0043] The first layer (surface layer): first lay a slurry with high mica content (mica powder 80wt%, aramid fiber 20wt%) on the bottom of the mold, and form a uniform thin layer by suction filtration or slurry spreading method, and the thickness is controlled at 0.2mm.

[0044] Second layer (inner layer): Then add slurry with higher fiber content (aramid fiber 30wt%, mica powder 70wt%), and control the thickness at 0.5mm to ensure that the inner layer has higher mechanical strength.

[0045] The third layer (surface layer): Finally, a layer of slurry with high mica content is laid as the surface layer, and the thickness is also controlled at 0.2mm.

[0046] S7. Drying and curing

[0047] The formed aramid fiber mica paper is carefully taken out, placed on a drying rack, and dried in an oven at a temperature of 100°C for 2 hours. Drying and curing also include hot pressing curing, specifically, the hot pressing temperature is controlled at 120°C, the pressure is 1MPa, and the time is 10 minutes.

[0048] If you need to improve the wear resistance or water resistance of the surface, you can apply a coating. The coating material is selected from polyurethane and epoxy resin, and is applied by brush or spray. The coating thickness is controlled at 0.1mm and cured at room temperature or heated to 60℃ for 2 hours.

[0049] Example 2

[0050] The embodiment of the present invention provides a method for preparing aramid fiber mica paper, which specifically comprises the following steps:

[0051] S1. Raw material preparation

[0052] Prepare raw materials: 25 parts of aramid fiber, 75 parts of mica powder, 0.7 parts of carboxymethyl cellulose, 3 parts of acetic acid, 65 parts of deionized water, and 0.15 parts of vitamin C. The aramid fiber is preferably chopped fiber with a length of 4 mm and a diameter of 13 μm. The mica powder has a particle size of 75 μm and an acetic acid concentration of 5%.

[0053] S2. Surface treatment of aramid fiber

[0054] The aramid fiber was immersed in an acetic acid solution and stirred at room temperature for 1 hour. After treatment, the fiber was thoroughly washed with deionized water until it was neutral, so that active groups were generated on the surface of the aramid fiber, thereby enhancing the interfacial bonding between the fiber and the mica particles.

[0055] S3. Wet Forming

[0056] Prepare aramid fiber, mica powder, carboxymethyl cellulose and deionized water, add aramid fiber and mica powder into deionized water under stirring, then add carboxymethyl cellulose, control the stirring speed at 650r / min, the stirring time for 13 minutes, control the solid content of the mixture at 4wt%, and adjust the pH value to 6.5;

[0057] S4. Forming and initial dehydration

[0058] The mixture was poured into a pre-prepared mold, and a suction filtration device, a Buchner funnel, was used for preliminary dehydration under negative pressure, and then preliminary molding was performed, and preliminary dehydration was performed under negative pressure of -0.05MPa for 7 minutes. The thickness after preliminary molding was controlled at 2.5mm;

[0059] S5. Mechanical compression

[0060] Use a mechanical press or rolling equipment to gradually compress the material after preliminary dehydration in the press. The initial pressure is 0.5MPa, which is gradually increased to 2.0MPa. The compression time for each stage is 7 minutes, and the thickness of the compressed material is controlled at 0.7mm.

[0061] S6. Hierarchical structure design

[0062] During the molding process, aramid fiber and mica powder were added in different proportions in layers to design aramid fiber mica paper with a gradient structure. The mica powder content in the surface layer was increased to 83wt% to improve the insulation performance, and the aramid fiber content in the inner layer was increased to 33wt% to improve the mechanical strength and toughness.

[0063] The first layer (surface layer): first lay a slurry with high mica content (mica powder 80wt%, aramid fiber 20wt%) on the bottom of the mold, and form a uniform thin layer by suction filtration or slurry spreading method, and the thickness is controlled at 0.25mm.

[0064] Second layer (inner layer): Then add slurry with high fiber content (aramid fiber 30wt%, mica powder 70wt%), and control the thickness at 0.6mm to ensure that the inner layer has high mechanical strength.

[0065] The third layer (surface layer): Finally, a layer of slurry with high mica content is laid as the surface layer, and the thickness is also controlled at 0.25mm.

[0066] S7. Drying and curing

[0067] The formed aramid fiber mica paper was carefully taken out, placed on a drying rack, and dried in an oven at 110°C for 3 hours. Drying and curing also included hot pressing curing, specifically at a hot pressing temperature of 135°C, a pressure of 1.5 MPa, and a time of 13 minutes.

[0068] If you need to improve the wear resistance or water resistance of the surface, you can apply a coating. The coating material is selected from polyurethane and epoxy resin, and is applied by brush or spray. The coating thickness is controlled at 0.15mm and cured at room temperature or heated to 70℃ for 2 hours.

[0069] Example 3

[0070] The embodiment of the present invention provides a method for preparing aramid fiber mica paper, which specifically comprises the following steps:

[0071] S1. Raw material preparation

[0072] Prepare raw materials: 30 parts of aramid fiber, 80 parts of mica powder, 1.0 parts of carboxymethyl cellulose, 5 parts of acetic acid, 80 parts of deionized water, and 0.2 parts of vitamin C. The aramid fiber is preferably chopped fiber with a length of 6 mm and a diameter of 15 μm. The mica powder particle size is 100 μm, and the acetic acid concentration is 5%.

[0073] S2. Surface treatment of aramid fiber

[0074] The aramid fiber was immersed in an acetic acid solution and stirred at room temperature for 1 hour. After treatment, the fiber was thoroughly washed with deionized water until it was neutral, so that active groups were generated on the surface of the aramid fiber, thereby enhancing the interfacial bonding between the fiber and the mica particles.

[0075] S3. Wet Forming

[0076] Prepare aramid fiber, mica powder, carboxymethyl cellulose and deionized water, add aramid fiber and mica powder into deionized water under stirring conditions, then add carboxymethyl cellulose, control the stirring speed at 800 r / min, the stirring time for 15 minutes, control the solid content of the mixture at 5wt%, and adjust the pH value to 7;

[0077] S4. Forming and initial dehydration

[0078] The mixture was poured into a pre-prepared mold, and a suction filtration device, a Buchner funnel, was used for preliminary dehydration under negative pressure, and then preliminary molding was performed, and preliminary dehydration was performed under negative pressure of -0.05MPa for 10 minutes, and the thickness after preliminary molding was controlled at 3mm;

[0079] S5. Mechanical compression

[0080] Use a mechanical press or rolling equipment to gradually compress the material after preliminary dehydration in the press. The initial pressure is 0.5MPa, which is gradually increased to 2.0MPa. The compression time for each stage is 10 minutes, and the thickness of the compressed material is controlled at 1.0mm.

[0081] S6. Hierarchical structure design

[0082] During the molding process, aramid fiber and mica powder are added in different proportions in layers to design aramid fiber mica paper with a gradient structure. The mica powder content in the surface layer is increased to 85wt% to improve the insulation performance, and the aramid fiber content in the inner layer is increased to 35wt% to improve the mechanical strength and toughness.

[0083] The first layer (surface layer): first lay a slurry with high mica content (mica powder 80wt%, aramid fiber 20wt%) on the bottom of the mold, and form a uniform thin layer by suction filtration or slurry spreading method, and the thickness is controlled at 0.3mm.

[0084] Second layer (inner layer): Then add slurry with high fiber content (aramid fiber 30wt%, mica powder 70wt%), and control the thickness at 0.7mm to ensure that the inner layer has high mechanical strength.

[0085] The third layer (surface layer): Finally, a layer of slurry with high mica content is laid as the surface layer, and the thickness is also controlled at 0.3mm.

[0086] S7. Drying and curing

[0087] The formed aramid fiber mica paper is carefully taken out, placed on a drying rack, and dried in an oven at 120°C for 4 hours. Drying and curing also include hot pressing curing, specifically at 150°C, 2MPa, and 15 minutes.

[0088] If you need to improve the wear resistance or water resistance of the surface, you can apply a coating. The coating material is selected from polyurethane and epoxy resin, and is applied by brush or spray. The coating thickness is controlled at 0.2mm and cured at room temperature or heated to 80℃ for 2 hours.

[0089] The preparation of traditional aramid fiber composite materials often relies on a single molding method, such as only wet molding or hot pressing. This single method is difficult to take into account both the density and uniformity of the material. Although wet molding can better disperse the fibers and fillers, it is prone to problems such as unstable material structure and uneven precipitation of fibers and particles during the dehydration process. Mechanical compression, as a separate step, is often difficult to fully compress the already molded material, resulting in insufficient density and mechanical properties of the material. The present invention combines wet molding with mechanical compression, first achieving uniform dispersion of fibers and mica through wet molding, and then further improving the density and interfacial bonding of the material through mechanical compression, thereby overcoming the shortcomings of a single molding method.

[0090] In the prior art, the interfacial bonding between aramid fiber and inorganic filler (such as mica) is usually weak. This is because the surface of aramid fiber is relatively inert and the interaction with inorganic particles is poor, which makes the composite material prone to interfacial peeling when subjected to force. Although some technologies attempt to enhance interfacial bonding through surface modification, these modification methods often involve complex chemical treatments or use expensive reagents, which increase the preparation cost, and the modification effect is unstable, making it difficult to achieve consistent interfacial enhancement effects in large-scale production. The present invention uses simple acetic acid to surface treat aramid fiber, which can effectively introduce active groups and enhance the interfacial bonding between fiber and mica particles without significantly increasing costs and process complexity. This simple and effective treatment method overcomes the problem of insufficient interfacial bonding in the prior art, while having good operability and economy.

[0091] In the prior art, the structural design of composite materials is often homogeneous, that is, the ratio of fibers and fillers is evenly distributed in the material. This homogeneous structure makes it difficult to achieve a combination of multifunctionality, such as high mechanical strength and high insulation performance at the same time. Although some studies have attempted to achieve functional gradients through multi-layer composite materials, in actual operation, the bonding force between layers is weak, stratification is prone to occur, and the thickness and proportion of each layer are not precisely controlled, resulting in unstable material properties. The present invention realizes the preparation of functional gradient materials by controlling the ratio of aramid fiber and mica powder in different layers through layered structural design. For example, a high mica content in the surface layer improves the insulation performance, and a high aramid fiber content in the inner layer improves the mechanical strength and toughness. This design overcomes the shortcomings of the prior art that the homogeneous structure cannot take into account multifunctionality, realizes an optimized combination of material properties, and ensures the close bonding and thickness consistency of each layer through precise process control.

[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing aramid fiber mica paper, characterized in that: The specific steps include: S1. Raw material preparation Prepare raw materials: aramid fiber: 20-30 parts, mica powder: 70-80 parts, carboxymethyl cellulose: 0.5-1.0 parts, acetic acid: 1-5 parts, deionized water: 50-80 parts, vitamin C: 0.1-0.2 parts; S2. Surface treatment of aramid fiber The aramid fiber was immersed in an acetic acid solution and stirred at room temperature for 1 hour. After treatment, the fiber was thoroughly washed with deionized water until it was neutral, so that active groups were generated on the surface of the aramid fiber, thereby enhancing the interfacial bonding between the fiber and the mica particles. S3. Wet Forming Prepare aramid fiber, mica powder, carboxymethyl cellulose and deionized water. Add aramid fiber and mica powder into deionized water under stirring conditions, and then add carboxymethyl cellulose. The stirring speed is controlled at 500-800 r / min and the stirring time is 10-15 minutes. S4. Forming and initial dehydration The mixture is poured into a pre-prepared mold, and a suction filtration device, a Buchner funnel, is used to perform preliminary dehydration under negative pressure conditions, and then preliminary shaping is performed; S5. Mechanical compression Using a mechanical press or roller press, the initially dehydrated material is gradually compressed in the press; S6. Hierarchical structure design During the molding process, aramid fiber and mica powder were added in different proportions in layers to design aramid fiber mica paper with a gradient structure; S7. Drying and curing Carefully take out the formed aramid fiber mica paper, place it on a drying rack, and use an oven to dry it. The temperature is controlled between 100-120°C and the drying time is 2-4 hours.

2. The method for preparing aramid fiber mica paper according to claim 1, characterized in that: In the raw material preparation of step S1, the aramid fiber is preferably chopped fiber with a length of 3-6 mm and a diameter of 12-15 μm, the mica powder particle size is 50-100 μm, and the acetic acid concentration is 5%.

3. The method for preparing aramid fiber mica paper according to claim 1, characterized in that: In the step S3 wet forming, the solid content of the mixture is controlled at 3-5wt%, and the pH value is adjusted to 6-7.

4. The method for preparing aramid fiber mica paper according to claim 1, characterized in that: In the step S4 of forming and preliminary dehydration, preliminary dehydration is performed under a negative pressure of -0.05 MPa, the dehydration time is 5-10 minutes, and the thickness after preliminary forming is controlled to be 2-3 mm.

5. The method for preparing aramid fiber mica paper according to claim 1, characterized in that: In the step S5, the initial pressure of the mechanical compression is 0.5 MPa, which is gradually increased to 2.0 MPa. The compression time of each stage is 5-10 minutes, and the thickness of the material after compression is controlled to be 0.5-1.0 mm.

6. The method for preparing aramid fiber mica paper according to claim 1, characterized in that: In the layered structure design of step S6, the content of mica powder in the surface layer is increased to 80-85wt% to improve the insulation performance, and the content of aramid fiber in the inner layer is increased to 30-35wt% to improve the mechanical strength and toughness.

7. The method for preparing aramid fiber mica paper according to claim 1, characterized in that: The drying and curing in step S7 also includes hot pressing curing, and specifically the hot pressing temperature is controlled between 120-150° C., the pressure is 1-2 MPa, and the time is 10-15 minutes.

Citation Information

Cited By

  • Preparation method of high-temperature-resistant insulating material of multi-branched-chain aramid fiber bonded mica

    CN120535948A